2013
DOI: 10.1111/nph.12166
|View full text |Cite
|
Sign up to set email alerts
|

The response of the maize nitrate transport system to nitrogen demand and supply across the lifecycle

Abstract: SummaryAn understanding of nitrate (NO À 3 ) uptake throughout the lifecycle of plants, and how this process responds to nitrogen (N) availability, is an important step towards the development of plants with improved nitrogen use efficiency (NUE). NO À 3 uptake capacity and transcript levels of putative high-and low-affinity NO À 3 transporters (NRTs) were profiled across the lifecycle of dwarf maize (Zea mays) plants grown at reduced and adequate NO À 3 . Plants showed major changes in high-affinity NO À 3 up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 65 publications
7
104
0
2
Order By: Relevance
“…Under N deficiency, many N transporters and proteins mediating N metabolism have differential expression or accumulation (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012;Garnett et al 2013), although no specific genes mediating N uptake and assimilation were identified with differential expression in rice seedlings at the early stage of N limitation (Lian et al 2006). Here, we found eight genes regulating N assimilation with significant down-regulation at the transcriptional level in the ZD958 root after 12-day N deficiency (Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 76%
See 2 more Smart Citations
“…Under N deficiency, many N transporters and proteins mediating N metabolism have differential expression or accumulation (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012;Garnett et al 2013), although no specific genes mediating N uptake and assimilation were identified with differential expression in rice seedlings at the early stage of N limitation (Lian et al 2006). Here, we found eight genes regulating N assimilation with significant down-regulation at the transcriptional level in the ZD958 root after 12-day N deficiency (Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 76%
“…Plants can directly absorb various N compounds such as nitrate, ammonium, urea, amino acids, peptides, and proteins; however, nitrate is the predominant N absorbed by crops (Yuan et al 2007;Paungfoo-Lonhienne et al 2008;Näsholm et al 2009;Tegeder and Rentsch 2010;Wang et al 2012). Nitrate uptake from the soil is mediated by a series of transporters such as NRT1.1, NRT2.1 and NRT2.2 in the root (Wang et al 2012;Garnett et al 2013). After entry into the root system, nitrate is either directly transported to the shoot or reduced as ammonium by nitrate reductase and nitrite reductase, followed by synthesis of amino acids or other organic nitrogenous molecules with the glutamine synthetase and glutamate synthetase as initial catalysts (Lam et al 1996;Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst Soly NPF6.10 root expression was nitrate inducible, the Soly NPF6.9 expression behaved constitutively (Lauter et al , 1996). Root expression analysis of two maize co-orthologous genes grown under low and adequate nitrate nutrition showed no response of either gene in relation to N-nutrition throughout the whole lifecycle (Garnett et al , 2013). This emphasizes the complexity and variation in gene regulation in relation to nutrient uptake in crop plants with complex genomes, in comparison to a simple genome model plant such as Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…Plants were grown under a 14 h photoperiod at 25/20 • C temperature and 70/80% relative humidity (day/night). The light intensity at the canopy was 500 mol m −2 s −1 photons as described by Garnett et al (2013).…”
Section: Growth Chamber Experimentsmentioning
confidence: 99%